2006
DOI: 10.1002/j.2055-2335.2006.tb00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Unnecessary Medicines Stored in Homes of Patients at Risk of Medication Misadventure

Abstract: Background: The storage of unnecessary medicines poses safety concerns including patient confusion, inappropriate medication use and unintentional ingestion by children. Consumer storage and wastage of medicines is of concern to health practitioners and the Australian government. Aim: To describe, quantify, establish safety concerns, and estimate the cost of unnecessary medicines stored in patients' homes. Method: Patients discharged from two hospitals in 2002 who were part of a study of a community liaison ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Medications that were expired or no longer required by the patients were removed from patients' homes with their permision. 40 Any difficulties, problems or potential problems experienced by the patients were rectified or highlighted for primary care provider intervention.…”
Section: Clp Servicementioning
confidence: 99%
“…Medications that were expired or no longer required by the patients were removed from patients' homes with their permision. 40 Any difficulties, problems or potential problems experienced by the patients were rectified or highlighted for primary care provider intervention.…”
Section: Clp Servicementioning
confidence: 99%
“…The main reasons are that most of this medication lack the scientific research and clinical trials required to examine the safety of these drugs in each age group separately. Vuong & Marriott (2006) added that, children's vital organs are not developed or fully grown therefore the exposure to certain medications may lead to toxic side effects as the body is unable to metabolize the medication fully. These drugs increase the presence of active compounds in the body for a prolonged period and increase in their levels in the body, producing toxic effects.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Various reports across the globe revealed that, there is wastage of drugs and unnecessary holding of drugs, including those that were expired. 6,7 Expired drugs may not give the potential cure expected, consequently increasing the duration of morbidity. Improper storage of drugs can lead to potential loss of effectiveness.…”
Section: Introductionmentioning
confidence: 99%